2020
DOI: 10.1016/j.heliyon.2020.e04707
|View full text |Cite
|
Sign up to set email alerts
|

Oral disorders and ethnobotanical treatments: A field study in the central Middle Atlas (Morocco)

Abstract: The present study was conducted in the Moroccan central Middle Atlas in order to inventory the plants used in the treatment of oral diseases, as well as to document possible risks of intoxication. Thus, 58 herbalists in the region were surveyed to gather ethnomedical information about the plants used in natural remedies preparation. The expression of the data obtained was achieved through the calculation of different quantitative indices, such as: use value (UV), family use value (FUV), relative frequency of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 30 publications
4
34
1
Order By: Relevance
“…This result confirms those obtained by Agbankpé et al [11] and Dougnon et al [12] in which the practice of traditional medicine is much more reserved for older women in southern Benin. These results are also contrary to the findings of Najem et al [13] who proved that traditional medicine is more practiced by the male gender in Morocco. Similarly, it contradicts the findings of Mutie et al [14] in Kenya who showed that 66.67% of herbal medicine traders are male.…”
Section: Discussioncontrasting
confidence: 99%
“…This result confirms those obtained by Agbankpé et al [11] and Dougnon et al [12] in which the practice of traditional medicine is much more reserved for older women in southern Benin. These results are also contrary to the findings of Najem et al [13] who proved that traditional medicine is more practiced by the male gender in Morocco. Similarly, it contradicts the findings of Mutie et al [14] in Kenya who showed that 66.67% of herbal medicine traders are male.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, the medicinal plants recorded in our work were compared to those reported in ethnobotanical surveys carried out in the same study area (Jouad et al 2001, Mikou et al 2016, Youbi et al 2016 as well as in other regions of Morocco (Chaachouay et al 2019, El Hachlafi et al 2020, Haouari et al 2018, Harouak et al 2018, Najem et al 2020, Strathern 2002.…”
Section: Identification Of the Speciesmentioning
confidence: 81%
“…erefore, our survey showed that the most used plants in the Taza region were Origanum compactum, Mentha pulegium, Rosmarinus officinalis, Aloysia citrodora, Calamintha officinalis Moench, and Artemisia herba-alba Asso., while Artemisia huguetii, Mentha pulegium, Trigonella Antioxidant effect [28] Protection of gastric mucosal damage [29] Evidence-Based Complementary and Alternative Medicine [35] Gastroprotection [36] Antibacterial and antifungal [37] Antibacterial and antioxidant [38] Asteraceae [46] Antibiofilm and anticaries [47], radical scavenging and antioxidant activity [48] 6…”
Section: Discussionmentioning
confidence: 99%